Proactive Personality and Political Influence Behavior on the Career Success of Employees at the Curio Sub-District Office of Enrekang Regency - Dewi Pratiwi Indriasari; Sofyan Hamid Indar (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
Everyone who works in the organization wants career success The career success experienced by individuals is in accordance with the career path policy in each agency. The purpose of this study was to find out whether proactive personality influences employee career success, whether political influence behavior influences employee career success and whether proactive personality and political influence behavior influence employee career success. The sampling technique in this study used a saturated sample of 35 employees. In the data analysis technique using multiple linear regression analysis. The research results obtained are 1) proactive personality has a significant effect on employee career success 2) political influence behavior has a significant effect on employee career success and 3) proactive personality and political influence behavior simultaneously have a significant effect on Employee Career Success at the Curio District Office, Enrekang Regency. Keywords: Proactive Personality, Political Influence Behavior And Employee Career Success.